The Evolution of Research on International Public Opinion of China's Public Emergencies: A Visualized Analysis Based on CiteSpace Knowledge Mapping (The Journal of Medicine, Humanity and Media, 2024)
Objective：With the deepening of globalization and information technology, the international public opinion effects of China's emergency events are becoming increasingly prominent. Systematically reviewing the research progress in this field is crucial for countering Western media biases and enhancing national discourse power. Method: This study retrieves relevant CSSCI literature from the CNKI database and employs CiteSpace to create knowledge maps of research power, research hotspots, and their evolution. Conclusion: The year 2020 marked a turning point, where the COVID-19 pandemic drove an overall increase in research and led to a shift from focusing on Weibo public opinion analysis and emergency management to emphasizing the guidance of international public opinion and enhancing discourse power. This also spurred innovations in theoretical perspectives and research methods. The study also reveals issues such as dispersed research efforts and insufficient academic accumulation, with limited numbers of core authors and institutions, and the lack of a clear research community. Interdisciplinary collaboration needs to be strengthened. Future research should focus on interdisciplinary empirical exploration, methodological innovation, and promoting the construction of China's discourse system to enhance the ability to guide international public opinion.
Keywords: Public emergencies; International Public Opinion; Opinion Guidance; Knowledge Mapping; Visualized Analysis